A laser-equipped chamber for the assessment of sprint swimming traits in fishes - Zillig, Kenneth W.; Fukumoto, Jacqueline A.; McInturf, Alexandra G.; Burman, Scott G.; Steel, Anna E.; Cocherell, Dennis E.; Fangue, Nann A. (Frontiers in Ecology and Evolution, 2025)
Sprint swimming performance in fishes is relatively understudied despite its critical role in predation attempts, prey evasion, spawning events, and overcoming hydraulic challenges. Sprint swimming is characterized by fast acceleration, over a short distance and of limited duration. The bulk of sprint performance research uses analysis of high-speed recordings of fish behavior. While behavioral video analysis has improved, it is still expensive in both processing time and computational resources, limiting the ability to develop reaction norms for sprint performance which necessitate large sample sizes. Here we present a laser-gated sprint performance chamber (SPC) that improves upon past designs by introducing an adjustable number of lasers (≤ 25) that facilitates greater resolution on sprint performance. Use of customized arrangements can facilitate measurement of novel performance metrics of interest to a range of key questions (e.g., fatigue rate, residual anaerobic capacity, and sprint stamina). Using this chamber we quantified the sprint velocity, residual anaerobic capacity, sprint stamina, and fatigue rate of rainbow trout (Oncorhynchus mykiss), a widely distributed and studied species. We directly compared the results measured by our device to high-speed camera data collected simultaneously and found the velocity estimates from the sprint chamber to be highly accurate (R2 = 0.97). We also compared the sprint performance of individual rainbow trout with their individual UCRIT, a commonly measured metric of aerobic swimming performance. We found little correlation between the two traits, indicating that fish capable of rapid sprint swimming are not necessarily fast sustained swimmers. Finally, we defined and quantified three novel traits of sprint swimming performance: relative anaerobic scope, sprint stamina (the number of sprint events that can be elicited prior to performance decline), and fatigue rate (the rate of decline associated with repeated sprinting). The SPC is an adjustable platform for quantifying understudied elements of fish swimming physiology, improving design of fish passage infrastructure, and facilitating discoveries in how sprint performance changes with environmental conditions.